Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray terhadap Keaktifan dan Berpikir Kreatif Siswa dalam Pembelajaran Fisika - Antomi Saregar; Sely Saputri; Vandan Wiliyanti (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
This study investigated the effect of the Two Stay Two Stray (TSTS) cooperative learning model on students' learning activeness and creative thinking in physics learning. The study was grounded in the need to strengthen active participation and creative idea generation in Grade VIII physics, particularly on mechanical wave concepts. A quasi-experimental method with a nonequivalent control group design was employed. The sample consisted of 64 students of SMP Negeri 5 Bandar Lampung, with 32 students in the experimental class and 32 students in the control class. The experimental class learned using TSTS, whereas the control class received conventional instruction. Data were collected through a creative-thinking essay test, learning-activeness observation sheets, interviews, and documentation. Creative thinking was assessed through fluency, flexibility, originality, and elaboration, while activeness was observed through physical, mental, and social participation. The results showed that the experimental class outperformed the control class in both activeness (86.41% vs. 71.09%) and creative-thinking posttest scores (82.34 vs. 70.28). Independent-samples t-tests indicated significant differences in learning activeness, t(62)=5.03, p<0.001, and creative thinking, t(62)=4.86, p<0.001. The N-gain of creative thinking reached 0.70 in the experimental class and 0.49 in the control class. These findings imply that TSTS can be used as a structured cooperative strategy to increase peer interaction, expand information exchange across groups, and support creative responses in physics learning. Further studies are recommended to test TSTS across different physics topics, integrate it with digital or experiment-based media, and examine the quality of student interaction during group mobility.